The conservation-related biology and ecology of the leatherback turtle, dermochelys corilacea in Rantau Abang, Terengganu, Malaysia - Chan, Eng Heng (Kagoshima University, 2010)
This dissertation provides an analysis of the temporal and spatial trends exhibited in the Malaysian leatherback nesting population in Terengganu, addresses the most serious threats to the survival of the population, and through conservation-oriented research, formulates measures to counteract the declining trend observed in the population. Conservation measures which have been formulated and proposed have been translated into action by the appropriate federal and state agencies responsible for the conservation and management of sea turtles.